PHOTOMETRIC CLASSIFICATION OF THE MARGONI & STAGNI SUSPECTED VARIABLES V 58, V91 - Andronov, I. L.; Chikrigin, A. V.; Kimeridze, G. N. (Одеські астрономічні публікації, 2017)
V58 was found to be an eclipsing variable with P = 0.46771d(82), TMin = 2446421.795(5) and eclipse duration d ≈ 0.2P. V91 is a RRab type star with P = 0.3493d(11), T0 = 2446421.402(5), Max=13.32m, Min=14.21m, and an asymmetry f = 0.26(2). Finding charts with photographic magnitudes of comparison stars are presented.